LABORATORY ELECTROCHEMISTRY “MYSTERY BOX”: FROM PRE-SERVICE TEACHERS’ OBSERVATIONS TO INFERENCES THROUGH PREDICT-OBSERVE-EXPLAIN STRATEGY - Carla Morais; Cidália André; Joana Alves; Gildo Girotto Jr. (Química Nova)
Given the challenges associated with understanding electrochemistry content by engaging in prediction, observation, and explanation, laboratory activities can foster active participation and critical thinking, enabling individuals to proactively confront and revise their understanding. Since pre-service teachers should gain firsthand experience with predict-observe-based on a predict-observe-explain strategy, we propose a laboratory activity presented as a “mystery box” related to concentration cells coupled with an Arduino-based electronic data measurement system to identify how pre-service chemistry teachers move from observations to inferences in a qualitative research. Data was collected by written records and oral explanations during the practical interactions. Results suggest that the proposed laboratory activity allows pre-service chemistry teachers to access data and correct inferences related to electrochemistry content, promoting critical thinking. Data also showed a connection between the macroscopic and symbolic domains, and pre-service teachers recognized concepts associated with the activity, such as solution conductivity and the potential difference in chemical reactions, interpreting the system with prior knowledge, like electron flow direction and concentration cell components. However, additional strategies are needed for detailed and consistent observation and inference recording, enhancing the potential of such activities in favoring electrochemistry education in high schools.